2020
DOI: 10.1093/jofore/fvaa036
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Parametric and Nonparametric Fitting Procedures of Tree-Stem Taper with Alternative Definitions for Validation Data

Abstract: This study aims to evaluate the robustness of parametric and nonparametric procedures using alternative definitions of validation data for loblolly pine. Specifically, four data division strategies were implemented: random selection of one-third of the trees in the data set, selection of the smallest one-third of the trees by diameter at breast height (DBH), selection of the middle third of the trees by DBH, and selection of the largest third of the trees by DBH. Results indicate that tree taper was predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…As Figures 2 and 3 illustrate, MB and RMSE were similar among the different number of H-D ratio/DBH groups. Although H-D ratio has been shown to be related to crown/tree form, and tree taper usually varies by tree DBH, e.g., [8,9,19,20], we found that the uncertainty of prediction was not considerably reduced when grouping data based on H-D ratio or DBH. model fitting did not appreciably improve the prediction accuracy.…”
Section: Grouping Data Based On Taxonomic Rankcontrasting
confidence: 64%
See 3 more Smart Citations
“…As Figures 2 and 3 illustrate, MB and RMSE were similar among the different number of H-D ratio/DBH groups. Although H-D ratio has been shown to be related to crown/tree form, and tree taper usually varies by tree DBH, e.g., [8,9,19,20], we found that the uncertainty of prediction was not considerably reduced when grouping data based on H-D ratio or DBH. model fitting did not appreciably improve the prediction accuracy.…”
Section: Grouping Data Based On Taxonomic Rankcontrasting
confidence: 64%
“…Max and Burkhart [11] proposed using the squared ratio d 2 /DBH 2 as the dependent variable, but Yang and Burkhart [9] found that the model with the first order ratio d/DBH provided more accurate predictions. To be comparable with the Kozak [12] model, the model with the first order ratio was used in this study, which is…”
Section: Segmented Polynomial Regression Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, the primarily desired area of application in the Western Macedonian Lignite Center covers about 2500 ha. However, Yang and Burkhart (2020) found that withholding certain classes of DBH for parametric fitting approaches, i.e. the smallest or largest diameter trees, did not effectively influence the predictive ability of taper functions Eq.…”
Section: Discussionmentioning
confidence: 94%